Thermodynamic and kinetic characteristics of an a-amylase from Bacillus licheniformis SKB4 - Samanta, Saptadip; Das, Arpan; Haider, Suman Kumar; Jana, Arijit; Kar, Sanjay; Mohapatra, Pradeep Kumar Das; Pad, Bikash Ranjan; Mondal, Keshab Chandra (Acta Biologica Szegediensis, 2014)
An amylolytic bacterial strain, Bacillus licheniformis SKB4 produced maximum amylase at pH 6.5 at 42 °C, and at late stationary phase (24 h) of growth. Starch and peptone were found the best supporting carbon and nitrogen source with C:N ratio of 1:2 for amylase production. The purified enzyme was non-responsive to most of the metal ions except K+ and Mg++ (1.0 mM). The enzyme was stable and active at pH 6.5. The enzyme showed optimum temperature at 90 °C with 10 min of half life (t½) at 100 °C. The Q10 of the enzyme was 1.0. The thermodynamic principles like activation energy, free energy for substrate binding and transition state of the enzyme were found 31.53, 5.53 and -17.4 KJ/Mol of starch, respectively. The kinetic constant like Vmax, Km, K catand catalytic efficiency (Kcat/Km)for starch were found to be 1.04 μmol mg-1 min-1, 6.2 mg ml-1,2 × 103 S-1 and 3.22 × 102 ml mg-1 S-1,respectively. All these findings suggested that this amylase has unique characteristics for starch hydrolysis in respect to thermostability and kinetic properties.